Concept and sign of order as avarienty of legal act in the organs of internal affairs - Босенко, Майя Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article is dedicated to the research of the concept «an order» in the scientific works of domestic and foreign scientists - theorists, main features of this act are determined as well. The order is examined as a normatively-legal act and an act of law application, that is why the place of the order among the whole quantity of acts is outlined.